Hubungan Konsumsi Mi Instan, Junk Food, dan Aktivitas Fisik dengan Kejadian Obesitas Pada Remaja di SMKN 3 Bogor - Siraz, Nazira Andriani; Adyas, Ezria Ekafadhina; Nurlita, Asri Ismiyani; Dwinugraha, Ksatriadi Widya (Poltekkes Kemenkes Yogyakarta, 2025)
The prevalence of obesity continues to increase due to changes in energy balance caused by various factors. Risk factors for obesity consist of heredity, diet, lack of physical activity, age, gender and socio-economic factors. This study aims to determine the relationship between consumption of instant noodles, junk food and physical activity with the incidence of obesity in adolescents at SMKN 3 Bogor. This research used a cross-sectional design and was conducted on March 22 – June 12 2024 at SMKN 3 Bogor. The number of subjects selected in this research was 114 people using purposive sampling technique. The Spearman test results show that there is a significant relationship (p<0.05) between pocket money, junk food consumption and physical activity with the incidence of obesity in teenagers at SMKN 3 Bogor. On the other hand, the Spearman test results showed that there was no relationship (p>0.05) between age, gender and instant noodle consumption and the incidence of obesity in adolescents at SMKN 3 Bogor.